The Influence of Psychological Impact of Online Learning during Covid-19 on Student’s Academic Achievement: A Case Study at Vocational Higher Education - Hutomo Atman Maulana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This study aimed to determine the influence of psychological impact that consist of depression, anxiety, and stress in students due to online learning in vocational higher education conducted during the Corona virus disease 2019 (COVID-19) on student’s academic achievement. The samples in this study were 180 students of the Undergraduate Program Department of Commercial Administration of Politeknik Negeri Bengkalis. The Samples were taken using the purposive sampling technique focused solely on students who gained online learning in theory and practice courses since the use of online learning because of the COVID-19. The Data was collected using a DASS 42 instrument through online questionnaire. The results of this study showed that the psychological impact of depression, anxiety, and stress experienced by students because online learning does not have a partial significant effect but simultaneously affects academic achievement. Psychological impact contributed only 5.7% while the remaining 94.3% was influenced by other factors